Perspectives on Local Governance Across Europe
XXII, 375 p. 33 illus.
Keywords: This book focuses on local state-society relations, understood as institutionalised relations between local municipalities across Europe and individual, collective or corporate societal actors. It presents a typology of local state–society relations, and applies this to characterise the most relevant institutionalised relations between local government and societal actors at the municipal level in 22 European countries. The comparative volume will clarify whether or not patterns can be detected in the makeup of different types of networks; whether or not these patterns are country-specific or policy-specific; and why cases exist which are so distinct that they are not subsumable under a certain pattern. Taken together, this book will go beyond national typologies to emphasise the role of agency and innovation in particular policy sectors, providing a major contribution in the study of the local governance of Europe. It will appeal to scholars and students of local governance, public administration, urban planning and European studies. Björn Egner is Adjunct Professor at the Institute of Political Science, Technische Universität Darmstadt, Germany. His research interests include local politics, housing policy and fiscal policy. Hubert Heinelt is Professor of Public Administration, Public Policy and Urban Research at the Technische Universität Darmstadt, Germany. Between 2010 and 2013 he was President of the European Urban Research Association. Jakub Lysek is Assistant Professor in the Department of Political Science at Palacký University Olomouc, Czech Republic. His research interests include local politics and electoral behaviour. Patrícia Silva is Assistant Professor in the Department of Social, Political and Territorial Sciences at the University of Aveiro, Portugal. Her research interests include political parties, public administration, and local governance. Filipe Teles is Pro-Rector for Regional Development and Urban Policies at the University of Aveiro, Portugal. His research interests include governance, local administration, territorial reform and political leadership.